Biomaterial-Assisted Self-Healing for Crack Reduction in High-Performance Centrifugal Concrete Piles - Arian Adibinia; Hesam Dehghan Khalili; Mohammad Mehdi Mohebbi; Mohammad Momeni; Pezhman Moradi; Soleiman Ghouhestani; Ali Poorkarimi (Buildings)
Cracks in reinforced concrete structures compromise strength and durability, particularly in high-performance centrifugal concrete (HPC) piles, where degradation can become irreversible. Despite their high density and low permeability, HPC piles remain vulnerable to cracking, sulfate attack, and chloride penetration, necessitating innovative durability solutions. While self-healing concrete has been widely studied, its application in HPC piles remains unexplored, representing a critical research gap. This study investigates the synergistic use of Bacillus sphaericus bacteria and flax fibers to enhance crack healing, permeability reduction, and mechanical performance in HPC piles. In this research, HPC specimens were fabricated using a specialized centrifugal device and casting process. During the mixing phase, bacteria and flax fibers were incorporated into the concrete. The fresh mix was then spun to form the final specimens. To evaluate bacterial self-healing performance of specimens, controlled random cracks were induced using a compression testing machine. Thereafter, a series of compressive strength tests, 30 min water absorption tests (BS 1881), scanning electron microscopy (SEM) combined with energy dispersive X-ray spectroscopy (EDS), and EDS mapping (MAP) were conducted to evaluate self-healing efficiency. Results demonstrated that bacterial activation upon cracking led to calcium carbonate precipitation, effectively sealing cracks, reducing permeability, and enhancing compressive strength. Optimizing bacterial and fiber content further influenced water absorption and mechanical properties in both cubic and centrifugally cast specimens. This study bridges a critical gap by introducing biomaterial-based self-healing in HPC piles, offering a sustainable, cost-effective, and long-term strategy for enhancing the durability of deep foundation systems in aggressive environments.